2019
DOI: 10.1007/s13311-019-00719-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Fasting Mimicking Diet on MPTP-Induced Parkinson's Disease Mice via Gut Microbiota and Metabolites

Abstract: Parkinson's disease (PD) is strongly associated with life style, especially dietary habits, which have gained attention as disease modifiers. Here, we report a fasting mimicking diet (FMD), fasting 3 days followed by 4 days of refeeding for three 1-week cycles, which accelerated the retention of motor function and attenuated the loss of dopaminergic neurons in the substantia nigra in 1-methyl-4-phenyl-1,2,3,6-tetrathydropyridine (MPTP)-induced PD mice. Levels of brain-derived neurotrophic factor (BDNF), known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 72 publications
5
103
0
Order By: Relevance
“…Healthy mice that received feces from PD mice had deteriorated motor function and decreased striatal neurotransmitters compared to controls. Zhou et al (2019) observed less motor function decline and loss of dopaminergic neurons in the substantia nigra in PD mice that received a fasting mimicking diet (FMD) compared to ad-libitum-fed PD mice. Furthermore, they observed a higher striatal dopamine and serotonin concentration in PD mice that had received feces from FMD-fed control mice compared to phosphate-buffered solution (PBS)-gavaged or ad-libitum microbiota-gavaged PD mice.…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 98%
“…Healthy mice that received feces from PD mice had deteriorated motor function and decreased striatal neurotransmitters compared to controls. Zhou et al (2019) observed less motor function decline and loss of dopaminergic neurons in the substantia nigra in PD mice that received a fasting mimicking diet (FMD) compared to ad-libitum-fed PD mice. Furthermore, they observed a higher striatal dopamine and serotonin concentration in PD mice that had received feces from FMD-fed control mice compared to phosphate-buffered solution (PBS)-gavaged or ad-libitum microbiota-gavaged PD mice.…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 98%
“…47 In a chemically induced mouse model of PD, a fecal microbiota transfer leading to increased propionic and isobutyric acid levels correlated with increased dopamine levels. 48 Conversely, a recent study from Sampson et al demonstrated that transferring a human PD-derived microbiota into a mouse alphasynuclein overexpression PD model resulted in increased butyric acid and propionic acid levels, followed by an increase in PD-like symptoms, and administration of a mix of SCFAs into germ-free mice recapitulated some of the observed effects. 30 SCFAs are highly implicated in intestinal barrier integrity and immunological responses.…”
Section: Short-chain Fatty Acid Analysismentioning
confidence: 99%
“…Therefore, it is not surprising that fasting mimicking diets decrease dextran sulfate sodiuminduced inflammation and stimulate the commensal gut microbiota, leading to reduced IBD pathological changes in the intestines (113). Fasting mimicking diets are also able to reduce neuroinflammaton and to exert a protective effect (114). Fasting mimicking diets may increase butyrate, thereby exerting anti-inflammatory effects (114).…”
Section: Other Approaches That Can Modulate the Gut Microbiotamentioning
confidence: 99%